Sepiolite Enfolded Sulfur/ZnO Binary Composite Cathode Material for Li-S Battery - Kalaiselvi, Chelladurai; Subadevi, Rengapillai; Wang, Fu-Ming; Sivakumar, Marimuthu (Frontiers in Materials, 2020)
Lithium-Sulfur (Li-S) batteries have become an incredible challenge for the approaching age of high-vitality stockpiling gadgets. Nevertheless, one of the main specialized issues emerging in Li-S batteries is the polysulfide disintegration among electrodes and striking capacity limit. Here, sieved sepiolite (200 mesh sieve) has been favored as an added substance material to counter the above difficulties in the sulfur battery. The zinc oxide nanoparticles were prepared by co-precipitation method and a Sulfur/post-treated sieved Sepiolite/Zinc Oxide (S/PTSp/ZnO) nanocomposite was prepared by warmth treatment. The prepared composite was described by XRD, FTIR, RAMAN, SEM with EDAX, TEM, XPS, TG, and Electrochemical analysis. The S/PTSp/ZnO composite cathode exhibited an initial discharge capacity of 1,391 mAhg−1 and attained a stable capacity of 765 mAhg−1 at 200 cycles. In conclusion, Li-S batteries can be relied upon to capably build up the utilization of sulfur and limit the disintegration of polysulfides into an electrolyte.